Global entertainment media : a critical introduction - Artz, Lee (Malden, MA : John Wiley & Sons Inc, 2015)
This accessibly written and critical introduction investigates the crucial role that Global Entertainment Media has played in the emergence of transnational capitalism. Using case studies of action adventure movies and community media, it breaks down sophisticated theoretical concepts, including a concise explanation of cultural hegemony, into engaging and student-friendly commentary. Global Entertainment Media offers clear explanations of the complex relationship between international political economy, entertainment media, global culture, and cultural hegemony. Incorporating an array of features designed to facilitate students' engagement with the ideas and arguments presented, it includes fully integrated callout boxes with definitions of terms and concepts, and lists and summaries of global media. Perfectly balancing provocative criticism with clear explanations of complicated theories, and unpacking cultural hegemony as a primary analytical concept, this book will be essential reading for any student of international communication or global media. --Book Jacket.
Introduction: entertainment, television, and cultural hegemony -- 21st century capitalism and transnational relations -- Leading the charge: transnational planning -- Transnational media -- From regional to global: transnational media leaders -- Cultural hegemony: leadership with consent -- Power decentered: dominant diversity -- Superheroes to the rescue -- Media, democracy, and political power -- Conclusion: the reality of power.
Includes bibliographical references and index.
Keywords: Mass media and culture; Mass media and globalization; Culture and globalization; Mass media -- Influence; Mass media -- Political aspects